Transformasi Paradigma Kebijakan Publik: Integrasi Prinsip Hukum Progresif dalam Pembangunan Hukum Responsif di Indonesia - Evi Fitriani; Ahmad Ahsin Thohari; Irsyaf Marsal (Pusat Riset dan Inovasi Nasional, 2025)
This article discusses the transformation of the public policy paradigm in Indonesia through the integration of progressive legal principles in order to realize legal development that is responsive to the social needs of society. Progressive law, as initiated by Satjipto Rahardjo, emphasizes that the law must side with substantive justice and the needs of the people, not merely enforce rigid and procedural legal certainty. This research uses a normative juridical approach with qualitative analysis of various laws and regulations, legal doctrines, and relevant case studies. The results of the study show that the integration of progressive legal principles into public policy has great potential in bridging the gap between social reality and formalistic legal construction. However, the implementation of this principle is faced with a number of challenges, such as institutional resistance from conservative legal institutions, a legal education paradigm that is still legal-formalistic, and limited public participation in the legislative process. To overcome these obstacles, a comprehensive strategy is needed, including reforming the legal education curriculum, revitalizing law enforcement officials, strengthening the role of civil society, and optimizing information technology in the justice system. With these steps, legal transformation is expected to be not only structural, but also cultural and paradigmatic, so as to realize a national legal system that is more inclusive, fair, and relevant to the dynamics of contemporary Indonesian society.